Persistence of oral pre-exposure prophylaxis (PrEP) among adolescent girls and young women initiating PrEP for HIV prevention in Kenya. Issue 6 (3rd June 2021) - de Dieu Tapsoba, Jean; Zangeneh, Sahar Z.; Appelmans, Eline; Pasalar, Siavash; Mori, Kira; Peng, Lily; Tao, Janice; Drain, Paul; Okomo, Gordon; Bii, Stanley; Mukabi, James; Zobrist, Stephanie; et al.
ABSTRACT: The Determined, Resilient, Empowered, AIDS-free, Mentored, and Safe (DREAMS) Initiative aims to reduce HIV infections among adolescent girls and young women (AGYW) in Africa. Oral pre-exposure prophylaxis (PrEP) is offered through DREAMS in Kenya to eligible AGYW in high burden counties including Kisumu and Homa Bay. This study examines PrEP persistence among AGYW in high burden community-based PrEP delivery settings. We evaluated PrEP persistence among AGYW in the DREAMS PrEP program in Kisumu and Homa Bay using survival analysis and programmatic PrEP refill data collected between March through December 2017. Among 1, 259 AGYW who initiated PrEP during the study period, the median persistence time in the program was 56 days (95% CI: 49–58 days) and the proportion who persisted 3 months later was 37% (95% CI: 34-40%). Persistence varied by county ( p  < 0.001), age at PrEP initiation ( p  = 0.002), marital status ( p  = 0.008), transactional sex ( p  = 0.002), gender-based violence (GBV) experience ( p  = 0.009) and current school attendance ( p  = 0.001) at DREAMS enrollment. Persistence did not vary with orphan status, food insecurity, condom use, age at first sexual encounter or engagement in age-disparate sex at DREAMS enrollment. Targeted strategies are needed to improve AGYW retention in the PrEP program.